2016
DOI: 10.1111/bjop.12209
|View full text |Cite
|
Sign up to set email alerts
|

Dressing up posture: The interactive effects of posture and clothing on competency judgements

Abstract: Individuals often receive judgements from others based on their clothing and their posture. While both of these factors have been found to influence judgements of competency independently, their relative importance in impression formation is yet to be investigated. We address this by examining interactive effects of posture and clothing on four competency measures: confidence, professionalism, approachability, and likeliness of a high salary. Participants rated photographs of both male and female models pictur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 57 publications
0
19
0
1
Order By: Relevance
“…However, there was no control group, and this may have been a crucial omission. In a different study, when a neutral posture was included, competence ratings made by observers were in fact higher for people in HPPs than for people in LPPs, but they were highest in controls (Gurney, Howlett, Pine, Tracey, & Moggridge, 2017), suggesting that HPPs are not the best way to signal competence.…”
Section: Effects On the Actormentioning
confidence: 87%
See 2 more Smart Citations
“…However, there was no control group, and this may have been a crucial omission. In a different study, when a neutral posture was included, competence ratings made by observers were in fact higher for people in HPPs than for people in LPPs, but they were highest in controls (Gurney, Howlett, Pine, Tracey, & Moggridge, 2017), suggesting that HPPs are not the best way to signal competence.…”
Section: Effects On the Actormentioning
confidence: 87%
“…The findings on effects of body positions on observers also seem to be in line with the dominance‐prestige framework: Participants performing HPPs did not perform better in job interviews (e.g., Klaschinski et al, 2017). Further, participants in neutral body positions (that resemble UPs) received higher competence ratings than participants in HPPs (e.g., Gurney et al, 2017). However, we inferred this conclusion from studies that looked only at poses, and there are no posture studies that directly compared competence ratings of UPs with controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As formal clothing is associated with enhanced social distance, Slepian proposes that wearing formal clothing will enhance abstract cognitive processing. Gurney et al [41] confirmed that competency ratings of individuals vary by their posture [42,43,44] and their attire [45,46]. In their study they also confirmed an interaction effect of posture and clothing by showing that perceptions of people in different attire can be altered by the posture they adopt while wearing it.…”
Section: The Socio-psycological Impact Of Clothingmentioning
confidence: 66%
“…Posture-based personality judgements also interact with extrinsic cues like clothing; for example, individuals perceive actors in suits as more competent(Gurney et al, 2017).4 Perception of use, available at https://www.cambridge.org/core/terms. https://doi.org/10.1017/9781009029049 Downloaded from https://www.cambridge.org/core.…”
mentioning
confidence: 99%